Man and the biosphere UNESCO - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Man and the Biosphere (MAB) is part of a broader UNESCO initiative on the environment and its resources, comprising well-established programmes of international scientific cooperation in such areas as oceans and their resources, coastal zones,...